2020
DOI: 10.5194/angeo-38-231-2020
|View full text |Cite
|
Sign up to set email alerts
|

Early morning peaks in the diurnal cycle of precipitation over the northern coast of West Java and possible influencing factors

Abstract: Abstract. The diurnal cycles of precipitation over the northern coast of West Java have been studied using the Tropical Rainfall Measuring Mission (TRMM) Real Time Multi-satellite Precipitation Analyses (TMPA-RT) products with records spanning from 2000 to 2016, with emphasis on the occurrences of early morning precipitation peaks. Diurnal precipitation over the study area during November to March is basically characterized by precipitation peaks that occur in the afternoon to evening time (15:00–21:00 LT), bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…The resulting increase in column moisture over the SMC is characterized by positive total moisture flux convergence anomalies, indicative of positive net precipitation (Figure 1f). This finding is consistent with previous studies, showing that cold surges can propagate deep into the tropics, triggering convection and precipitation, which eventually lead to heavy rainfall and flood events (Hattori et al., 2011; Lim et al., 2017; Wu et al., 2013; Xavier et al., 2020; Yulihastin et al., 2020). In addition, the CES‐induced moist environment over the SMC suggests its potential role in providing additional moisture and energy for the intensification and propagation of the MJO, which will be investigated in the subsequent section.…”
Section: Resultssupporting
confidence: 93%
“…The resulting increase in column moisture over the SMC is characterized by positive total moisture flux convergence anomalies, indicative of positive net precipitation (Figure 1f). This finding is consistent with previous studies, showing that cold surges can propagate deep into the tropics, triggering convection and precipitation, which eventually lead to heavy rainfall and flood events (Hattori et al., 2011; Lim et al., 2017; Wu et al., 2013; Xavier et al., 2020; Yulihastin et al., 2020). In addition, the CES‐induced moist environment over the SMC suggests its potential role in providing additional moisture and energy for the intensification and propagation of the MJO, which will be investigated in the subsequent section.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figures 3 and 4, the average phase speed of diurnal offshore precipitation propagation is 3-4 m s −1 near the coast, similar with the magnitudes in the land breeze or the cold pool outflow [28,30,32,61]. The phase speed of 8-9 m s −1 further offshore is noticeably distinguished from the magnitude of background wind, and indicates other possible factors such as gravity waves, with a similar speed of roughly 8-15 m s −1 , as generated by land-sea thermal contrast or convection [21,24,[62][63][64][65].…”
Section: Diurnal Propagation Associated With Gravity Wavessupporting
confidence: 67%
“…As one of the regions with most active convection and great influences by factors such as MJO or convectively coupled equatorial waves (CCEWs), MC generates frequent precipitation all over the years, and the associated latent heat from rainfall becomes one of the main energy sources driving global circulation [16], which plays nonnegligible roles in global weather and climate [17][18][19][20]. The diurnal variation of rainfall is a common phenomenon in coastal regions, including MC; more specifically, it is often characterized by offshore propagation near the coasts, whose mechanisms are closely related to gravity waves [21][22][23][24], background-wind modulations [21,23,25], land-sea breezes [26][27][28][29], and cold pool outflows [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Wet days have a more intense and apparent offshore westward migration of precipitation with a phase speed of ∼10 ms −1 . The strong maritime diurnal cycle of precipitation with such long range has been documented in several locations around the world (Huang et al, 2018;Mapes et al, 2003;Yang & Slingo, 2001;Yokoi et al, 2019;Yulihastin et al, 2020). For example, Yokoi et al (2019) showed that long-lasting convective clusters over the west coast of Sumatra propagate westward at about ∼8-10 ms −1 .…”
Section: Figures 3a and 3b Show A Longitudinal Transect Of The Diurna...mentioning
confidence: 92%